Development of Treasures Number Learning Media to Develop Early Childhood Numeracy Skills 4-5 Years Old - Siti Rokayah; Ferdian Utama; Leli Fertiliana Dea (CV. Creative Tugu Pena, 2025)
This study aims to develop Number Treasure learning media made from plywood and test its effectiveness in improving numeracy skills of children aged 4-5 years at TK Arsya Bunda Bandar Mataram, Central Lampung. The research used Research and Development (R&D) method with 4D model (Define, Design, Develop, Disseminate). The subjects were 15 children aged 4-5 years. Data collection used observation, expert validation questionnaires, interviews, and documentation. Data analysis used quantitative techniques with Likert scale and qualitative descriptive. Media expert validation results obtained